Global warming : the hard science - Harvey, Leslie Daryl Danny, 1956- (Harlow : Prentice Hall, 2000)
This book is divided into three parts: Introduction; Climatic change; and The science-policy interface.
Keywords: Global warming; Greenhouse effect; Atmospheric; Carbon cycle; Biogeochemistry; Global warming; Greenhouse effect, Atmospheric; Carbon cycle (Biogeochemistry)